Facial neuralgia - Hoa, Jacques Hui Bon (British Homeopathic Journal, 1977)
When confronted with a case of facial neuralgia, and if this is seated on the right and there is an absence of other indications, there is a strong chance that the remedy will be Kalmia latifolia. If it is seated on the left and the eyeball is affected, the remedy is Spigelia. If the pain is of the electrical discharge type and seated at the level of the left upper lip, or else of the lower left gum, the remedy is Colocynthis. When the pain appears gradually and disappears slowly, whether seated on the right or on the left, the remedy is Stannum. If the pain is aggravated by draughts, think of Nux vomica. If it is aggravated by the cold, think of Silicea. Sulphur and Calcarea carbonica are the two remedies for facial neuralgia which are at the same time the constitutional remedy for the patient, an exception to the rule which says that facial neuralgia is never treated constitutionally.Facial pain of vascular ogirin, on the other hand, is treated constitutionally, like migraine (Sepia, Aurum, Pulsatilla).